Biogeography of Drosophila (Diptera: Drosophilidae) in East and Southeast Asia. Issue 1 (13th June 2015) - Robert Liu, Fu-Guo; Tsaur, Shun-Chern; Huang, Hsiao-Ting
Abstract : The causes of high biological diversity in biodiversity hotspots have long been a major subject of study in conservation biology. To investigate this matter, we conducted a phylogeographic study of five Drosophila (Diptera: Drosophilidae) species from East and Southeast Asia: Drosophila albomicans Duda, D. formosana Duda, D. immigrans Sturtevant, D. melanogaster Meigen, and D. simulans Sturtevant. We collected 185 samples from 28 localities in eight countries. From each collected individual, we sequenced the autosomal extra sex comb gene ( esc ) and seven mitochondrial genes, including nicotinamide adenine dinucleotide hydrate-reductase dehydrogenase subunit 4 ( ND4 ), ND4L, tRNA-His, tRNA-Pro, tRNA-Thr, partial ND5, and partial ND6 . Phylogenetic analyses using maximum- likelihood and Bayesian methods revealed interesting population structure and identified the existence of two distinct D. formosana lineages (Southeast Asian and Taiwanese populations). Genetic differentiation among groups of D. immigrans suggests the possibility of endemic speciation in Taiwan. In contrast, D. melanogaster remained one extensively large population throughout East and Southeast Asia, including nearby islets. A molecular clock was used to estimate divergence times, which were compared with past geographical events to infer evolutionary scenarios. Our findings suggest that interglacial periods may have caused population isolation, thus enhancing population differentiation more strongly for some of the Drosophila species. The population structure of each Drosophila species in East and Southeast Asia has been influenced by past geographic events.